Oxytocin, Feeding, and Satiety - Sabatier, Nancy; Leng, Gareth; Menzies, John (Frontiers in Endocrinology, 2013)
Oxytocin neurones have a physiological role in food intake and energy balance. Central administration of oxytocin is powerfully anorexigenic, reducing food intake and meal duration. The central mechanisms underlying this effect of oxytocin have become better understood in the past few years. Parvocellular neurones of the paraventricular nucleus project to the caudal brainstem to regulate feeding via autonomic functions including the gastrointestinal vago-vagal reflex. In contrast, magnocellular neurones of the supraoptic and paraventricular nuclei release oxytocin from their dendrites to diffuse to distant hypothalamic targets involved in satiety.The ventromedial hypothalamus, for example, expresses a high density of oxytocin receptors but does not contain detectable oxytocin nerve fibres. Magnocellular neurones represent targets for the anorexigenic neuropeptide α-melanocyte stimulating hormone. . In addition to homeostatic control, oxytocin may also have a role in reward-related feeding. Evidence suggests that oxytocin can selectively suppress sugar intake and that it may have a role in limiting the intake of palatable food by inhibiting the reward pathway.